Impact of Chinese fiscal decentralization on industrial green transformation: From the perspective of environmental fiscal policy - Qi, Yawei; Zou, Xianya; Xu, Mo (Frontiers in Environmental Science, 2022)
To accomplish the goals of carbon mitigation, industrial green transformation is an inevitable requirement for achieving high-quality economic development. Based on the data of 30 provinces in China from 2007 to 2017, this paper uses projection pursuit model and entropy method to calculate the industrial green transformation and Chinese fiscal decentralization. It further employs static and dynamic spatial Durbin model to explore the impact of Chinese fiscal decentralization on industrial green transformation by the environmental fiscal policy. The study finds that: 1) China’s industrial green transformation presents an unbalanced state with high in the east and low in the west, which has a positive spatial spillover among provinces. 2) Fiscal decentralization is significantly conducive to the industrial green transformation, while the spatial spillover of fiscal decentralization is negative. Moreover, fiscal decentralization affects the industrial green transformation by environmental fiscal policy, in of which environmental fiscal expenditure is the main path. 3) From the perspective of heterogeneity of fiscal decentralization, the impact of fiscal expenditure decentralization in promoting industrial green transformation is significantly greater than that of fiscal revenue decentralization. In terms of heterogeneity of regional location, fiscal decentralization in the eastern and central regions plays a role in accelerating industrial green transformation, while it has an obstacle impact in the western region. In terms of market-based heterogeneity, Fiscal decentralization in high-market areas facilitates the green transformation of industry, while in low-market areas is the opposite.